Equatorial stratospheric jet and its coupling with the tropospheric jet (MAUSAM, 1975)
Analysis of 100 rocket wind measurements over Thumba (India) indicates the existence of an equatorial stratospheric jet stream in 32-42 km range throughout the year. Similar data from other equatorial meteorological rocket stations show that the ESJ is a worldwide phenomenon, confined to the equatorial region only. There are seasonal variations in the intensities and heights of the ESJ. Strong wind shears exist in the vicinity of the ESJ varying between 8 mps/km in the post monsoon season to 22 mps/km in the winter. Covariance of' u’ and v' which is a measure of the angular moment11mtransport, IS computed from surface up to 55km. The height profile of the covariance shows a southward transport of angular momentum maintains the ESJ.       Intensities of the ESJ and the tropical easterly jet (TEJ) are highly correlated. The heights of the tropopause and the stratopause, which influence thetropospheric and stratospheric jets respectively, are negatively correlated. The instabilities near the ESJ is highly correlated with the instability near the TEJ seven days later, suggesting that the disturbance near the ESJ travels down to the levels of the TEJ in seven days. From these correlations it is inferred that the tropospheric and stratospheric jets are strongly coupled, just as the polar front jet and the Arctic stratospherioc jet are coupled.